Color compatibility between dental structures and three different types of ceramic systems - Ioana-Sof; Razvan Ghinea; Horatiu A. Colosi; Javier Ruiz-López; Maria M. Perez; Rade D. Paravina; Diana Dudea (BMC, 2021)
Abstract Background To assess color compatibility between dental structures (human enamel and dentine) and three different types of ceramic systems. Methods Samples (1 and 2 mm-thick) of extracted tooth (containing dentine and enamel areas) and three ceramic systems with different shades and opacities (HT-High Translucent, T-Translucent) were prepared for this study: Vita Suprinity-VS (HT, T; A1, A2, A3, A3.5, B2, C2, D2) (Vita Zahnfabrik); Vita Enamic-VE (HT, T; 1M1, 1M2, 2M2, 3M2) (Vita Zahnfabrik) and Noritake Super Porcelain EX-3-NKT (A1, A2, A3, A3.5, B2, C2, D2) (Kuraray Noritake Dental). Reflectance measurements of all samples were performed over black backgrounds using a non-contact spectroradiometer (SpectraScan PR-670, Photo Research) under a CIE 45°/0° geometry. CIE L*a*b* color parameters were measured and CIELAB/CIEDE2000 color differences (ΔE00/ΔE* ab) and corresponding Coverage Error (CE) of ceramic system for dentine or enamel samples were calculated. Color data was analyzed using one-way ANOVA and post-hoc multiple comparisons tests. CE values were interpreted by comparisons with available 50:50% acceptability color threshold (AT) for dentistry. Results Statistically significant differences in lightness were found among all ceramic systems and human dentine (p < 0.001), while no significant differences were registered between enamel and VSHT, T and VEHT. 1 mm dentine showed no statistical differences with VST and VSHT for a* coordinate, while 2 mm dentine showed no significant differences (p > 0.05) with VEHT. Thin samples (1 mm) of dentine and enamel showed significant statistical differences (p < 0.05) for b* coordinate with less translucent materials (NKT, VET and VST). For dentine samples, none of the ceramic materials provided a CE lower than AT. VSHT provided the best CE for 1 mm-thick (CE00 = 1.7, CEab = 1.9) and for 2 mm-thick (CE00 = 2.3; CEab = 2.5) enamel samples. Conclusions Color coordinates of evaluated esthetic ceramic systems were statistically different from those of human dentine in almost all cases. The evaluated ZrO2 lithium silicate glass-ceramic (VS), with its two levels of translucency, provided lower CE values with human enamel samples while conventional feldspathic ceramic (NKT) and hybrid ceramic systems (VE) demonstrated a better color compatibility with dentin samples.